How did we find out about atoms? - Asimov, Isaac, 1920-1992.; Wool, David (New York : Walker, 1976)
Discusses the concept of atoms and evidence of their existence accumulated since the time of the Greeks.
Includes index.
Booklist.
School Library Journal.
6.9
6.9
5-8.
Keywords: Atoms -- Juvenile literature; Atoms; Atoms